If 2 is added to seven times a number and equals 8 more than six times a number what is the number
Answers
Seven times a number is 7x; 6 times a number is 6x and then solve7x+2=6x+8X+2=8X=6
Your word equation turned into an operation would be: 2+7n=8+6n. To complete this equation you have to balance it out so only n would be put on one side. So, try subracting 6n on both sides so it can be on the same side as 7n:2+7n-6n=8+6n-6n.Therefore the 6n on the right side has now switched over to the left. Then, you need to switch the 2 onto the right side by subtracting it on both sides as well:2+7n-6n-2=8-2The 2 has now been switched. After, subtract 7n-6n=1n, and 8-2=6. The equation then becomes:1n=6.To isolate n from 1, divide 1n by 1 and 6 by 1. Your equation afterwards should be: n=6/1, or as simplified: n=6.
How do I expand r(r-r2) the 2 is meant to be r squared
Answers
The explicit formula for a sequence isan=−1+3(n−1)
What is the 55th term of the sequence?
Answers
Step-by-step explanation:
Hence, the 55th term of the sequence is 161.
Lindsay paid $4.40 for 1 gallon of ice cream. At this rate, what 1 quart cost? What would 1 pint cost? Please explain.
Answers
each pint would cost 55 cents if u divide 1.10 by two because I think that there are two pints in one quart.
Which function below is the inverse of f(x) = x2 − 9?
Answers
Let f(x)=y y= Make x the subject of the formula; y+9= x= So, the inverse of the function is thus;
f (x)=y y=2x-9
X Y -2 -15 y=2 (-2)-9 y=-4+-9 y=-15
-1 -11 y=2 (-1)-9 y=-2+-9 y=-11
0 -9 y=2 (0)-9 y=0+-9 y=-9
1 -7 y=2 (1)-9 y=2+-9 y=-1
2 -5 y=2 (2)-9 y=4+-9 y=-5
Here is all the work
Which expression is equivalent to (7x - 5 ) - ( 3x - 2)?
Answers
Distribute the minus sign into the second parenthesis to get 7x-5-3x+2. Then combine like terms to get 4x-3